2009
DOI: 10.1021/jf9015202
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulatory, Antiinflammatory, and Antioxidative Effects of Protocatechuic Acid in Diabetic Mice

Abstract: Content of protocatechuic acid (PA) in eight locally available fresh fruits was analyzed, and the protective effects of this compound in diabetic mice were examined. PA at 1%, 2%, and 4% was supplied to diabetic mice for 8 weeks. PA treatments significantly lowered plasma glucose and increased insulin levels. PA treatments at 2% and 4% significantly lowered plasminogen activator inhibitor-1 activity and fibrinogen level; increased plasma activity of antithrombin-III and protein C; decreased triglyceride conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 31 publications
3
57
0
4
Order By: Relevance
“…In addition, it also reduces plasma C-reactive proteins and von Willebrand factor levels, interleukin-6, tumor necrosis factor-a, and monocyte chemoattractant protein-1 levels in heart and kidney (Lin et al 2009). Based on their experimental findings, Lin et al 2009 suggested that PCA was able to ameliorate complications in metabolic disorders through its beneficial effects like triglyceride-lowering, anticoagulatory, antioxidative and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it also reduces plasma C-reactive proteins and von Willebrand factor levels, interleukin-6, tumor necrosis factor-a, and monocyte chemoattractant protein-1 levels in heart and kidney (Lin et al 2009). Based on their experimental findings, Lin et al 2009 suggested that PCA was able to ameliorate complications in metabolic disorders through its beneficial effects like triglyceride-lowering, anticoagulatory, antioxidative and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, syringic acid possesses anti-obesity, antiinflammatory and anti-steatotic effects via the regulation of lipid metabolic and inflammatory genes (Ham et al, 2016). Also, protocatechic acid has shown anti-inflammatory effect (Lin et al, 2009). Treatment with protocatechic acid inhibits significantly different biological parameters like hind paw edema, granuloma exudates formation, and arthritis index in carrageenan edema, cotton pellet granuloma, and Freund's adjuvant arthritis, respectively.…”
Section: Azedarach Extract Had Shown Important Antibacterial Activmentioning
confidence: 99%
“…It is well established that they actively exhibit anticancer and antioxidant effects and possess anti-inflammatory, antimutagenic, and antiallergic properties. [18][19][20][21]. Among of these phytochemicals, gallic acid (3,4,5-trihydroxy benzoic acid; GA) has antiinflammatory and antiallergic properties.…”
Section: Introductionmentioning
confidence: 99%